Early and Late Rehabilitation and Physical Training in Elderly Patients After Cardiac Surgery - Claudio Macchi; Francesco Fattirolli; Raffaele Molino Lova; Andrea Conti; Maria Luisi; Rosanna Intini; Renato Zipoli; Costanza Bürgisser; Lorenzo Guarducci; Giulio Masotti; Gian Franco Gensini (2007)
Macchi C, Fattirolli F, Molino Lova R, Conti AA, Luisi MLE, Intini R, Zipoli R, Burgisser C, Guarducci L, Masotti G, Gensini GF: Early and late rehabilitation and physical training in elderly patients after cardiac surgery. Am J Phys Med Rehabil 2007;86:826–834. Objective: Few randomized trials have enrolled patients who have undergone cardiac surgery, and even fewer have included patients aged 75 yrs or more. Furthermore, the optimal timing of cardiac rehabilitation for postsurgical patients has not yet been codified. The aim of this study was to verify whether rehabilitation outcomes are also favorable in postsurgical patients aged 75 yrs or more and whether an early rehabilitation program is as effective and safe as a late one. Design: Three hundred patients who underwent cardiac surgery, 27.7% of whom were at least 75 yrs old, were randomly assigned to a rehabilitation program starting within the second week after operation or within the fourth week. All events occurring during the rehabilitation program or in the following year were recorded. Results: During the rehabilitation program, new-onset atrial fibrillation was significantly more frequent in the early rehabilitation group, independent of age class, and anemia was significantly more frequent in older patients, independent of rehabilitation timing. At the end of the rehabilitation program, more than 90% of patients showed significant increases in walking distance, and during the follow-up, no significant difference was found with regard to mortality, nonfatal events, functional ability, or control of cardiovascular risk factors, independent of rehabilitation timing and age class. Conclusions: This study provides evidence that in selected patients who have undergone cardiac surgery, rehabilitation outcomes are also favorable in patients aged 75 yrs or more, and an early rehabilitation program is as effective and safe as a traditionally late one.